2019
DOI: 10.1093/mnras/stz1803
|View full text |Cite
|
Sign up to set email alerts
|

Black hole and neutron star mergers in galactic nuclei: the role of triples

Abstract: Nuclear star clusters that surround supermassive black holes (SMBHs) in galactic nuclei are thought to contain large numbers of black holes (BHs) and neutron stars (NSs), a fraction of which form binaries and could merge by Kozai-Lidov oscillations (KL). Triple compact objects are likely to be present, given what is known about the multiplicity of massive stars, whose life ends either as a NS or a BH. In this paper, we present a new possible scenario for merging BHs and NSs in galactic nuclei. We study the evo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 114 publications
3
36
0
Order By: Relevance
“…BBHs in triple or quadruple systems can undergo Lidov-Kozai oscillations [211,212] that may expedite the GW inspiral of the binary. Such systems can either exist in the galactic field with a stellar-mass outer perturber [213][214][215][216][217][218][219] or in galactic nuclei with a supermassive BH as the tertiary component [220][221][222][223]. Though most modeling of hierarchical stellar systems does not include robust predictions for mass ratio distributions of merging BBHs, certain models find galactic field triples with asymmetric masses for the inner BBH to have a merger fraction that is about twice as large as their equalmass counterparts [213].…”
Section: Astrophysical Formation Channels For Gw190412mentioning
confidence: 99%
“…BBHs in triple or quadruple systems can undergo Lidov-Kozai oscillations [211,212] that may expedite the GW inspiral of the binary. Such systems can either exist in the galactic field with a stellar-mass outer perturber [213][214][215][216][217][218][219] or in galactic nuclei with a supermassive BH as the tertiary component [220][221][222][223]. Though most modeling of hierarchical stellar systems does not include robust predictions for mass ratio distributions of merging BBHs, certain models find galactic field triples with asymmetric masses for the inner BBH to have a merger fraction that is about twice as large as their equalmass counterparts [213].…”
Section: Astrophysical Formation Channels For Gw190412mentioning
confidence: 99%
“…The two main channels to BBH mergers are believed to be field binary star evolution, e.g., [2,3], and dynamical encounters. Dynamical mergers can occur in globular clusters [4,5], galactic nuclei [6][7][8], and in gas disks in galactic nuclei [9][10][11][12][13][14][15][16][17]. Mergers involving > 50 M ⊙ black holes (BHs) are unlikely to involve field binary stars [18].…”
mentioning
confidence: 99%
“…It has been suggested that a significant amount of binary black-hole (BH) mergers detectable by Advanced LIGO (aLIGO; [1]) and Advanced Virgo (aVirgo; [2]) may happen in galactic nuclei [3][4][5] or in surrounding gas disks [6][7][8]. The recent announcement by the Zwicky Transient Facility [9] further strengthens this possibility.…”
Section: Introductionmentioning
confidence: 99%
“…[27] for a review of different formation scenarios). Different authors have investigated this problem in different context, ranging from galactic nuclei (e.g., [4,5,[28][29][30][31]), to dense stellar clusters (e.g., [32,33]), to isolated field stars (e.g., [34][35][36][37][38][39][40][41]).…”
Section: Introductionmentioning
confidence: 99%